Relationship Between Short Umbilical Cord Length and Adverse Pregnancy Outcomes. (3rd March 2016) - Yamamoto, Yuriko; Aoki, Shigeru; Oba, Mari S.; Seki, Kazuo; Hirahara, Fumiki
Abstract: To investigate how umbilical cord length relates to pregnancy outcomes, we retrospectively analyzed data from 89, 042 deliveries recorded in the Japan Society of Obstetrics and Gynecology Successive Pregnancy Birth Registry System. We included term deliveries in which vaginal birth was attempted. Umbilical cord length was categorized into four groups: less than the first percentile, from the first percentile to less than the 10th percentile, from the 10th percentile to less than 25th percentile, and from the 25th percentile to less than the 75th percentile, which constituted the control group. Cord lengths of 33, 43, 48, 63 cm corresponded to the first, 10th, 25th, and 75th percentile values of the cord length distribution, respectively. Statistically significant differences were observed in the rate of unplanned cesarean delivery for all three short cord groups compared to control. There was a higher odds ratio for unplanned cesarean delivery as the umbilical cord became shorter.